Machining process of striped velvet - LIANG YONG; GE ZHENGLIN; LI DONG; YAO JINYU; ZHANG DONGHUA (2015)
The invention discloses a machining process of striped velvet. The machining process comprises the following steps: after a white blank is fed into a warehouse and is turned over, pre-forming the white blank, wherein 0.3%o.w.f of a fluffing agent in the pre-forming process; furring by using a furring machine, and completely tensioning and removing float hair in the furring process; reforming by using the forming machine, dyeing in a jar after being reformed, increasing the pressure in the dyeing process, and washing off waste cotton in grooves; taking off the fabric from the jar, and drying, wherein 2%o.w.f of a softening additive is added in the treatment process; ironing and shearing, and completely shearing off waste fur after being ironed; reforming again, and coiling and inspecting. The striped velvet produced by using the machining process is clear in strip and free of waste fur in the grooves.